POTENSI JUS JERUK NIPIS (CITRUS AURANTIFOLIA) SEBAGAI BAHAN PENGKELAT DALAM PROSES PEMURNIAN MINYAK NILAM (PATCHOULI OIL) DENGAN METODE KOMPLEKSOMETRI - Arkie Septiana A.; Frans Arienata H.; Andri Cahyo Kumoro (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2012)
Patchouli oil is one of the export commodities that have high economical value for Indonesia. In general, patchouli oil obtained from the hydrodistillation of patchouli leaves. Most industries are still using patchouli oil refiners made of ferrous metal. As this process takes place at high temperatures, water vapor will contain a lot of dissolved oxygen that is corrosive and causes iron to rust easily. The rust will dissolve in patchouli oil obtained and led to the resulting of dark oil and patchouli aroma becomes weaker. This situation led to a lower market price of patchouli oil. One method that can be used to purify is complexometry method with citric acid as the chelating agent. This certainly not familiar to farmers, therefore this study tried to simplify this process by finding a material that easily found by the common people. Orange juice contains citric acid which is enough to be used as a chelating agent, other than that lemon is a fruit that are easy to obtain in the community at abundant and the price is cheap. Therefore lemon juice was chosen as an alternative chelating material. The purpose of this study was to determine the influence of operating temperature, concentration of the chelating agent and the stirring time in the chelating process and find out the extent to which lemon juice can be used as a chelating agent. The treatments tested consisted of (1) the concentrations of citric acid, which are 0.5%, 1%, 2% and 4%; (2) Temperatures operation of the refinery. That are 30oC, 50 oC, and 75 oC, (3) agitation times, namely 15, 30, 45, 60, 75, and 90 minutes. Assessment of the results of purification is based on clarity, levels of Fe2+, and the content of the main components in patchouli oil refining results. Purification results showed that the increase in temperature causes the formation of complex ions faster to achieve equilibrium. The increase in the concentration of the citric acid led to complex ion formation process more quickly to achieve phase equilibrium. The best concentration was 1% combined with the use of temperature of 75 oC. Refined patchouli oil results have Fe2+ levels as low as 22.731 ppm. Based on the physical traits, the main constituent component content, and the Fe2+ content, refined patchouli oil meets the requirements of the Indonesian National Standards.